CARE-MS II Follow-up: Improvements with Alemtuzumab Maintained for 4 Years - Nichols, Emma Hitt (MD Conference Express, 2014)
Improvements in annualized relapse rate (ARR) and Expanded Disability Status Scale (EDSS) score were maintained throughout 4 years following treatment with alemtuzumab for 2 years in patients with relapsing-remitting multiple sclerosis (RRMS) who relapsed on prior therapy. This article presents data from the Extension Protocol for Multiple Sclerosis Patients Who Participated in Genzyme-Sponsored Studies of Alemtuzumab trial [NCT00930553; Hartung H-P et al. ECTRIMS 2014 (poster P043)].